Evaluation of the Program for Providing Local Supplementary Food to Pregnant Women with Chronic Energy Deficiency at Dosay Health Center, Jayapura District, 2023 - Homer, Marlina; Tingginehe, Rosmin Mariati; Bouway, Dolfinus; M, Novita; M, Sarce; R, Yacob (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to examine the evaluation of the supplementary feeding program for pregnant women with chronic energy deficiency from the input aspect, process aspect and output aspect in the Dosay Public Health Center working area, Jayapura Regency. This type of research is descriptive using qualitative methods. The results of this research state that from the input aspect (Human Resources, Financing and Infrastructure) there are still obstacles to financing. The budget provided by the Jayapura District Health Service is still very minimal so that the provision of additional food can only be carried out once a week even though it should be 3 times a week according to the Technical Guidelines. Likewise, there are very minimal infrastructure for the operationalization of this program. The process aspect of planning has gone well for pregnant women who come to have their health checked at the health center. It is also important to record and check the health of pregnant women who have not or did not come to the health center. Distribution and storage have gone well. Monitoring is carried out by the head of the community health center in collaboration with the Jayapura district Health Service and YP2KP Unicef. Recording is carried out regularly and in detail, and reporting uses the E-PPBGM application. In general, there are still many shortcomings and limitations, but the local supplementary feeding program has been running well and can provide benefits for pregnant women who take part in this program.